2001
DOI: 10.1038/labinvest.3780264
|View full text |Cite
|
Sign up to set email alerts
|

TCL1 Oncogene Expression in B Cell Subsets from Lymphoid Hyperplasia and Distinct Classes of B Cell Lymphoma

Abstract: Activation of the TCL1 oncogene has been implicated in T cell leukemias/lymphomas and recently was associated with AIDS diffuse large B cell lymphomas (AIDS-DLBCL). Also, in nonmalignant lymphoid tissues, antibody staining has shown that mantle zone B cells expressed abundant Tcl1 protein, whereas germinal center (GC; centrocytes and centroblasts) B cells showed markedly reduced expression. Here, we analyze isolated B cell subsets from hyperplastic tonsil to determine a more precise pattern of Tcl1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 33 publications
6
121
0
Order By: Relevance
“…The transformation of pre-B cells of Em-myc transgenic mice is enhanced by v-Ha-ras and v-raf (Alexander et al, 1989). The BLs, on the other hand, are characterized by deregulated c-myc mainly owing to the 8:14 translocation, which juxtaposes c-myc to Ig heavy chain locus and high TCL1 expression (Said et al, 2001;Kiss et al, 2003). TCL1 transgenic mice develop Burkitt-like lymphoma with high penetrance (Bichi et al, 2002;Hoyer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation of pre-B cells of Em-myc transgenic mice is enhanced by v-Ha-ras and v-raf (Alexander et al, 1989). The BLs, on the other hand, are characterized by deregulated c-myc mainly owing to the 8:14 translocation, which juxtaposes c-myc to Ig heavy chain locus and high TCL1 expression (Said et al, 2001;Kiss et al, 2003). TCL1 transgenic mice develop Burkitt-like lymphoma with high penetrance (Bichi et al, 2002;Hoyer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…TCL1 transgenic mice develop B-cell malignancies such as Burkitt-like lymphoma, diffuse large B-cell lymphomas (DLBCLs), B-cell leukemias and follicular lymphomas (Bichi et al, 2002;Hoyer et al, 2002). TCL1 is also expressed in human B-and T-cell-derived tumors (Said et al, 2001;Kiss et al, 2003). The capacity of TCL1 to promote cell survival and growth has been attributed to its AKT-activating properties (Pekarsky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…32 The authors postulated that the deleterious effects of HIV on the host immune system could be responsible for the different clinical outcomes in AIDS vs non-AIDS patients with lymphoma. 20,32,33 In the context of B-lymphocyte development, an early immunohistochemical study of AIDS-related lymphomas proposed three phenotypic patterns corresponding to centroblasts, late germinal center/early postgerminal center B cells, and postgerminal center Bcells. 34 Another study, which included cases of both AIDS-related diffuse large B-cell lymphoma and Burkitt lymphoma, has suggested that there may be a shift away from the more chemoresistant lymphomas of postgerminal center origin because of the better immune function conferred by highly active antiretroviral therapy.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…Dysregulated expression of TCL1 is a frequent molecular alteration in non-Hodgkin lymphomas (NHLs) that arise by transformation of germinal center (GC) B-cells (Teitell et al, 1999;Narducci et al, 2000;Said et al, 2001). Supporting an etiologic role in transformation, dysregulated expression of TCL1 in transgenic mouse B-cells throughout all stages of B-cell development promotes a spectrum of GC B-cell lymphoma subtypes that metastasize (Hoyer et al, 2002;Shen et al, 2006) or aggressive marginal zone-derived B-cell chronic lymphocytic leukemia (Bichi et al, 2002;Klein and Dalla-Favera, 2005;Yan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%